Parents Role in Growing an Interest in Reading - Nuragung Prayiti, Siti Syifa; Danugiri, Dadang (Universitas Negeri Padang, 2021)
This research are aiming to describe how the role of parents in fostering children’s reading interest in Anggrek Early Childhood Education Adiarsa Timur and children’s reading interest in Anggrek Early Childhood Education Adiarsa Timur. This research uses a qualitative approach with a case study method. This research was conducted in Anggrek Early Childhood Education Adiarsa Timur. The subject of the research is the source od information consisting of three parents of student, and the source of infomant consisting of one principal and one educator. Determination of research subjects using porposive sampling techniques. Research data obtained through observation, interviews, documentation studies, and triangulation. The research stages consist of orientation phase, exploration stage, and member check stage. Data analysis consists of data collection, data reduction, data display, and final conclusions. The result of research showed that parents have an important role as the first and foremost educator in fostering children’s interest in reading early on. The thing that parents can do at home is to give an example to children that reading is important, give special time to read together, and buy books that children love with reading materials that are appropriate to the age of the child. And the children’s interest in reading in Pre-school Anggrek Adiarsa Timur is very high, students in Anggrek Early Childhood Education Adiarsa Timur have a high sense of curiosity which makes them eager to learn to read. High interest needs support from several aspects such as learning resources, learning environment, dan learning facilities. Developed intererst will greatly influence behavior not only during the childhood period, but also afterwards, because it is very important for parents to foster children’s interest in reading early on.Keywords: The role of parents, Interest in reading, Early Childhood Education